Issues of Monitoring Methodology of Administrative Justice - Danielyan, Gevorg (Bulletin of Yerevan University C: Jurisprudence, 2022)
The article examines the scientific foundations of a comprehensive analysis and evaluation of the components of administrative justice. Criteria for evaluating the effectiveness of administrative procedure were put forward based upon the findings of this research․ Not only has it a theoretical significance, but rather a practical one, as it allows to evaluate the entire system of administrative procedure, to identify the existing gaps and shortcomings, as well as to suggest fundamental ways of resolving the issues raised, as effectively as possible. The article analyzes the relevant precedent decisions of the ECHR, as well as the decisions of the Constitutional Court, the positions of international expert institutions and the contemporary approaches of narrowly focused specialists. As a result, to the extent possible, the criteria necessary for the effective monitoring of administrative justice were put forward in a systemized way. It is also worth mentioning, that those criteria have been developed based on the particularities of the domestic legal foundations of administrative justice and of their practical application. According to the conclusion put forward in the article, the presence of a monitoring methodology does not exclude the possibility of research from new angles. It is just that from a purely scientific-practical standpoint, the monitoring methodology is extremely necessary so to guarantee the needed comprehensiveness of the analysis.